EDUCATION IN THE ERA OF INFORMATION CHALLENGE - M. V. Kudina; L. B. Logunova; Yu. Yu. Petrunin (Высшее образование в России)
The article presents an analysis of changes in the basic orientations of the education system in the information age, in the context of dialogue of cultures and transdisciplinarity of scientific research. In these conditions education should be a continuous process, a way of life (activity) of each person, his self-education, self-creation. Therefore, the most important task of school is the development of students' ability to learn and form their need for self-education. To solve this problem it is necessary to create an innovative school, creative (dialogical) pedagogy, and a complex multifunctional educational environment. As one of the tools of creative pedagogy a pilot innovation project of a social science textbook for secondary school was offered at the School of Public Administration Lomonosov Moscow State University.